2016
DOI: 10.5296/jas.v4i3.9331
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Perceptions on Climate Variability and Adaptation Strategies to Climate Change in Cinzana, Mali

Abstract: Several studies predict that climate change will highly affect the African continent. These changes in climate and climate variability may be challenging issues for future economic development of the continent in general, and particularly in the region of sub Saharan Africa. Offering a case study of Sahelian zone of Mali in the present study aimed to understand farmers" perceptions of climate variability and change and to evaluate adaptation options used by farmers in the Cinzana commune of Mali. One hundred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 39 publications
5
10
0
Order By: Relevance
“…The model also provides a convenient closed form for underlying choice probabilities, with no need of multivariate integration, making it simple to compute choice situations characterized by many alternatives (Hausman and McFadden 1984). It was highlighted by Touré et al (2016) and confirmed by the current survey that farmers in the Cinzana area combine different agriculture coping strategies. Therefore, to analyze the farmers' adaptation strategies, it was necessary to categorize them into several classes based on the number of adaptations strategies adopted.…”
Section: Analytical and Theoretical Frameworkmentioning
confidence: 52%
See 4 more Smart Citations
“…The model also provides a convenient closed form for underlying choice probabilities, with no need of multivariate integration, making it simple to compute choice situations characterized by many alternatives (Hausman and McFadden 1984). It was highlighted by Touré et al (2016) and confirmed by the current survey that farmers in the Cinzana area combine different agriculture coping strategies. Therefore, to analyze the farmers' adaptation strategies, it was necessary to categorize them into several classes based on the number of adaptations strategies adopted.…”
Section: Analytical and Theoretical Frameworkmentioning
confidence: 52%
“…This result is in line with several studies conducted in West Africa. Touré et al (2016) found that 94.1% of farmers perceived a decrease in the length of the rainy season witch implicitly means an increase in dry season in Cinzana. Maddison (2006) reported that farmers perceived the change in the beginning and the end of rainy season in seven sub-Saharan African countries including Senegal, Burkina Faso and Niger.…”
Section: Farmer's Perception Of Climate Changementioning
confidence: 99%
See 3 more Smart Citations